Gut Microbiome as a Novel Treatment Strategy for Psoriasis - Zając, Marlena; Borowiecka, Monika; Gruca, Dariusz; Buksak, Dagmara; Wróblewski, Wiktor (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Psoriasis is a skin disease that develops following chronic inflammatory signaling and keratinocyte hyperproliferation. The pathogenesis of psoriasis is compound and not yet fully understood. Several studies concerning gut microbiota composition and its role in disease pathogenesis recently demonstrated significant alterations among psoriatic patients. This study aims to highlight the latest scientific evidence regarding the gut microbiome alterations of psoriatic patients, as well as the state of knowledge in terms of microbiome-targeted therapies as promising preventive and therapeutic tools for psoriasis. Brief description of the state of knowledge: The current state of knowledge indicates that the main causes of psoriasis may be a genetic predisposition, as well as many immunological and environmental factors, including dysbiosis of the intestinal microflora. The article covers clinical and experimental studies which indicate that gut microbiota dysbiosis concerning diversity as well as the composition of the microbiome is the potential causal factor of psoriasis and the gut microbiota may serve as a promising prevention/therapy target for psoriasis patients. Conclusions: This review highlighted a strong link between psoriasis and the gut microbiota, to add new knowledge for discovering the relationship between the altered intestinal microbiota in psoriasis patients. Despite all of these interesting findings, there are a lot of limitations and challenges that future studies should face. More precise and greater studies need to be done to fully understand the potential of microbiota-aimed therapies.